Pupil‐size alterations induced by photodisruption during femtosecond laser–assisted cataract surgery. Issue 2 (February 2015) - Jun, Jong Hwa; Hwang, Kyu Yeon; Chang, Sung Dong; Joo, Choun‐Ki
Abstract : Purpose : To measure miosis after femtosecond laser pretreatment of cataract surgery and determine correlative factors. Setting : Department of Ophthalmology and Visual Science, Seoul St. Mary's Hospital, College of Medicine, and Catholic University of Korea, Seoul, South Korea. Design : Cross‐sectional study. Methods : Images extracted from surgical videos of femtosecond laser pretreatment and phacoemulsification were used to measure the pupil area. Quantitative analysis of pupil constriction was performed by comparing consecutive images obtained at the initiation of each procedure. Potential factors related to pupil constriction were examined, including laser parameters and anatomic measurements. Results : The study enrolled 56 eyes. The mean pupil area decreased by 29.7% during the time it took to shift between procedures (shifting time). The total laser treatment duration was highly correlated with the reduction in the pupil area ( r = −0.433, P = .001). The amount of intraoperative miosis was significantly correlated with the duration of lens fragmentation by the femtosecond laser ( r = −0.416, P = .001) and of primary incision creation ( r = −0.289, P = .031). Pupil constriction was correlated with patient age ( r = −0.398, P = .002) and the laser capsulotomy–pupil margin distance ( r = 0.395, P = .003), but not with suction‐on time ( r = −0.012, P = .930) or shifting time ( r = −0.091, P = .506). Conclusions : The pupil area decreased significantly after femtosecond laser pretreatment of cataract surgery. Intraoperative miosis was most significantly correlated with laser pretreatment duration and patient age. Financial Disclosure : No author has a financial or proprietary interest in any material or method mentioned.